Valuation of spectrum for mobile broadband services: Engineering value versus willingness to pay - Bengt G. Mölleryd; Jan Markendahl (International Telecommunications Society (ITS), 2011)
Radio spectrum is a vital asset and resource for mobile network operators. With spectrum in the 800 and 900 MHz bands coverage can be provided with fewer base station sites compared to higher frequency bands like 2.1 and 2.6 GHz. With more spectrum, i.e. wider bandwidth, operators can offer higher capacity and data rates. Larger bandwidths means that capacity can be provided with fewer base station sites, i.e. with lower cost. Operators that acquire more spectrum in existing or new bands can re-use existing sites for capacity build out. Engineering value is one way to estimate the marginal value of spectrum. The calculation of engineering value is based on comparison of different network deployment options using different amounts of spectrum. This paper compare estimates of engineering value of spectrum with prices paid at a number of spectrum auctions, with a focus on Sweden. A main finding is that estimated engineering value of spectrum is much higher than prices operators have paid at spectrum auctions during the last couple of years. The analysis also includes a discussion of drivers that determine the willingness to pay for spectrum.
Keywords: O14; K23; M11; 330; Radio spectrum; mobile communications; spectrum valuation; spectrum allocation; mobile broadband; marginal value of spectrum; engineering value